BACKGROUND AND PROSPECTS FOR THE OPERATION OF BATCH DISTILLATION - Lombira Echevarria, J. (1998)
Present contribution constitutes a review that shows the results of bibliographic research carried out about the simulation, design and optimization of batch. Distillation operation. It is analyses the present state of the art of this operation, contrasting its recent achieved results with difficulties that still exist in this area. The different batch distillation columns configurations that have been developed recently, such as the inverted column , middle vessels, multiple effects , extractive and azeotropic batch distillation columns are reviewed.